Are rural smallholders ready for agricultural digitalization? Farmer (In)competencies and the political economy of access in digital agricultural extension and advisories in Northern Ghana - Abdulai, Abdul-Rahim (Routledge, 2024)
Digitalization and digital agricultural extension and advisories are heralded to transform the conditions of smallholder farmers by increasing access to practical knowledge and information. However, critical questions on inclusivity and inaccessibility for farmers persist. This chapter uses a mixed-method approach—surveys of 386 farmers and three focus groups—in Northern Ghana to examine the barriers to farmers' utilization of digital agricultural extension and advisories and the underlying political-economic drivers. Farmers perceived the lack of digital literacy as the main barrier, as most of them do not have 'the ability to' undertake basic tasks, such as Internet browsing, following Interactive Voice Response, using a computer, social media, and sending short message services. The chapter argues that the lack of (digital) literacies results from deeply rooted political and economic structures in educational inequities that create literacy divides among farmers. Ultimately, the lingering digital illiteracy and divide undermine smallholders' access—ability to benefit—and power to influence digitalization futures. Thus, this chapter questions the inclusivity of digital agricultural extension and advisories and calls for matching digitalization processes to the realities of farmers by focusing on advisories that require minimal digital competencies and incorporating digital literacy/training programs into interventions. This work empirically contributes to the nascent agricultural digitalization literature as it critically positions the challenges to inclusive digitalization within broader political-economic structures dictating digital inequities.